Synthesis, Characterization And Structural Studies Of Palladium(Ii) Complexes With Some Substituted Phosphine And Arsine Ligands - Mohidin Yahya, Hamdya Farhana (2018)
The reaction between PdCl2(MeCN)2 with substituted phosphine and arsine ligand lead to the formation of palladium (II) complexes through the substitution of the labile MeCN group. Most of the complexes are mononuclear complexes except for tris-(p-methylphenyl)arsine ligand it manages to obtain both mononuclear and dinuclear complex.